2011
DOI: 10.1111/j.1365-2486.2011.02468.x
|View full text |Cite
|
Sign up to set email alerts
|

Major changes in forest carbon and nitrogen cycling caused by declining sulphur deposition

Abstract: Sulphur (S) and nitrogen (N) deposition are important drivers of the terrestrial carbon (C) and N cycling. We analyzed changes in C and N pools in soil and tree biomass at a highly acidified spruce site in the Czech Republic during a 15 year period. Total S deposition decreased from 5 to 1.1 g m À2 yr À1 between 1995 and 2009, whereas bulk N deposition did not change. Over the same period, C and N pools in the Oa horizon declined by 116 g C and 4.2 g N m À2 yr À1 , a total decrease of 47% and 42%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 64 publications
4
79
1
1
Order By: Relevance
“…Contrary to previous paired studies (e.g., [13]), we did find a higher C stock in the forest floor of the beech stand compared to the spruce stand. In an earlier study, we documented partial loss of forest floor C in the spruce stand as a result of recovery from acidification [54]. In the early 1990s, forest floor C mass was 58 t·ha −1 , comparable to the current beech stand, but it has since declined by 47%.…”
Section: Tree Species Effects On C Cyclingmentioning
confidence: 77%
See 1 more Smart Citation
“…Contrary to previous paired studies (e.g., [13]), we did find a higher C stock in the forest floor of the beech stand compared to the spruce stand. In an earlier study, we documented partial loss of forest floor C in the spruce stand as a result of recovery from acidification [54]. In the early 1990s, forest floor C mass was 58 t·ha −1 , comparable to the current beech stand, but it has since declined by 47%.…”
Section: Tree Species Effects On C Cyclingmentioning
confidence: 77%
“…This assumption might be violated, given the significant decline of forest floor C in the spruce stand noted above [54]. It is difficult to predict whether the spruce soil is currently in a steady state; thus, further calculation might be biased by the annual net loss of C from soil.…”
Section: Tree Species Effects On C Cyclingmentioning
confidence: 99%
“…Although SO 2 emissions have declined across Europe and eastern North America since the 1990s (Oulehle et al, 2011) and in China since 2005 (Fang et al, 2013), the contribution…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that soil acidification is a major problem in Chinese grassland and agricultural systems (Zhao et al 2009;Yang et al 2012), although the rate of acid deposition has reduced across Europe and North America since the 1990s (Oulehle et al 2011). For instance, anthropogenic acid deposition decreased soil pH by 0.63 units, on average, in the surface soil layer across northern China's grasslands during the last two decades (Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%